Fractal Antenna Design for Multiple Applications - M, Vasujadevi; Akhil Teja, K; Divya, G; Sai Shanmukh, VV; R Dheeraj, K (International Journal of Engineering and Technology, 2018)
The sudden development in in wireless applications has leveled up the use of antennas. Multiband antennas are used to operate at different frequencies for the reliability in various applications. This paper presents design of a novel fractal antenna for multiband applications. Attributes of proposed antenna are simulated using Ansoft HFSS. Due to the homogeneous property in the design of proposed fractal receiving wire it has the various multiband applications. Proposed Antenna design consists of FR4_epoxy material with dielectric constant of 4.4, height 1.6 mm. The operating frequency is taken as 2.4GHz. The antenna is simulated. The proposed antenna resonates at different frequencies. The results are measured and return losses are compared. Here the geometry of fractal antenna is analyzed for the C band resonating at 6.2 GHz, X band resonating at 11.9 GHz and Ku band resonating at 13.8 GHz for S11<-10db.Â Â